The Effect of TikTok Live Streaming Shopping on Online Consumer Trust - Kholifah, Kholifah; Trifiyanto, Kabul (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Purchasing decisions are a process that begins when consumers recognize a need, look for options, then evaluate alternatives and then choose certain products and services. Purchasing decisions are formed based on consumer perceptions of a company's offerings and its brand. Various studies have indicated that social media is an efficient marketing tool to influence consumers. In the midst of intense business competition, business actors must continue to follow developments in social media trends. One of the new features introduced by TikTok is Live Streaming, which can be used by businesses as a marketing strategy. Live Streaming Shopping (LSS) is the latest trend that allows businesses to interact in real-time with consumers. This research aims to evaluate the impact of LSS on online consumer trust, identify the influence of trust on purchasing decisions, and analyze the impact of LSS on purchasing decisions, both directly and indirectly through the level of trust in the TikTok social media platform. This research was conducted by interviewing respondents who had followed and made purchasing decisions via Live Streaming Shopping on the TikTok social media platform. This type of research is explanatory research which uses quantitative methods. Next, the data was analyzed using the Path Analysis technique to assess the influence of the variables studied, both directly and indirectly.